Female Sensuality on Screen - Ade Naura Intania; Dwi Ajeng Widarini; Bayquni (Program Studi Ilmu Komunikasi Universitas Serang Raya, 2022)
Mass media is one of the important things in human life to get information and entertainment. Mass media, one of which is television, has been around for a long time and has used women as an attraction. Women are used for their bodies and sensuality in television programs to make them more attractive and serve as entertainment content. This study aims to determine the semiotic analysis of the exploitation of women's sensuality and to find out the semiotic representation of the exploitation of women's sensuality in the Tonight Show NET.TV program, especially the episode on February 21, 2020. The method used is Roland Barthes' Semiotics and the theory of Gender, Expression, and Feminism as theory supporting this research. In general, the results of the analysis of this study found that the denotative, connotative, and mythical meanings contained in the NET.TV Tonight Show Program were seen from several signs such as the appearance of female guest stars, facial expressions, and dialogue between the host and guest stars that showed sexual context so that the show is entertaining and funny. This ultimately represents the exploitation or use of women's sensuality even in the form of jokes or chatter. For that, a great awareness is needed not to use women in the mass media industry, as well as educating the public about gender equality.